Bone Marrow–derived Cells and Biophysical Stimulation for Talar Osteochondral Lesions: A Randomized Controlled Study. (October 2014) - Cadossi, Matteo; Buda, Roberto Emanuele; Ramponi, Laura; Sambri, Andrea; Natali, Simone; Giannini, Sandro
Background: Osteochondral lesions of the talus (OLT) frequently occur after ankle sprains in young patients participating in sports activities. These injuries may lead to chronic pain, joint swelling, and finally osteoarthritis, therefore, surgical repair is frequently needed. A collagen scaffold seeded with bone marrow–derived cells (BMDCs) harvested from patient's iliac crest and implanted into the OLT through a single arthroscopic procedure has been recently proposed as an effective treatment option. Nevertheless, BMDCs, embedded in an inflammatory environment, tend to differentiate toward a fibroblast phenotype with a consequential loss of mechanical characteristics. Biophysical stimulation with pulsed electromagnetic fields (PEMFs) has been shown to promote anabolic chondrocyte activity, stimulate proteoglycan synthesis, and reduce the release of the most relevant pro-inflammatory cytokines. The aim of this randomized controlled trial was to evaluate the effects of PEMFs on clinical outcome in patients who underwent BMDCs transplantation for OLT. Methods: Thirty patients affected by grade III and IV Outerbridge OLT underwent BMDCs transplantation. After surgery, patients were randomly assigned to either experimental group (PEMFs 4 hours per day for 60 days starting within 3 days after operation) or control group. Clinical outcome was evaluated with (American Orthopaedic Foot and Ankle Society) AOFAS score, Visual Analog Scale (VAS), and Short Form-36 (SF-36). Results: Significantly higher AOFAS score was recorded in the experimental group both at 6 or 12 months follow-up. At 60 days and 6 and 12 months follow-up, significant lower pain was observed in the experimental group. No significant difference was found in SF-36 between groups. Conclusion: A superior clinical outcome was found in the experimental group with more than 10 points higher AOFAS score at final follow-up. Biophysical stimulation started soon after surgery aided patient recovery leading to pain control and a better clinical outcome with these improvements lasting more than 1 year after surgery. Level of Evidence: Level II, prospective comparative study.